Gaze and voice as love objects - Salecl, Renata, 1962-; Žižek, Slavoj (SIC (Durham, N.C.) ;, 1996)
The gaze entices, inspects, fascinates. The voice hypnotizes, seduces, disarms. Are gaze and voice part of the relationship we call love ... or hate? If so, what part? How do they function? This provocative book examines love as the mediating entity in the essential antagonism between the sexes, and gaze and voice as love's medium. The contributors proceed from the Lacanian premise that "there is no sexual relationship," that the sexes are in no way complementary, and that love - figured in the gaze and the voice - embodies the promise and impossibility of any relation between them